Principles and Methods of Organizing Lessons in Higher Education Using the CREAM Strategy - Mamatkulova, Nilufar (The Lingua Spectrum, 2025)
This article analyzes and highlights the role and significance of the CREAM strategy (Creativity, Reflective, Effective, Active and Motivation) in organizing an effective educational process in higher education. In particular, it discusses the evolution of the concept of didactic principles – from their origin to 21st-century education skills. The article explores opportunities for developing students’ creative potential, encouraging independent thinking, fostering active participation in the learning process, and supporting them through intrinsic motivation. Practical examples are provided to demonstrate how the core principles of the CREAM strategy – creative approach, reflective thinking, effectiveness, active involvement, and the integration of motivation – impact the quality and efficiency of education. The article also offers recommendations for organizing the educational process based on the CREAM strategy: the use of interactive methods, development of students’ independent and collaborative work skills, and transforming lessons into a student-centered approach through active learning. The author conducts an in-depth analysis of didactic principles, pedagogical approaches, and modern language teaching methods, substantiating the relevance of the CREAM strategy in contemporary education.